1989
DOI: 10.1007/bf01913033
|View full text |Cite
|
Sign up to set email alerts
|

Thermal and other studies on bivalent metal selenltes

Abstract: BaSeO3-Z5H~O(I); PbSeO 3.2HzO(ll ) and CdSeO~-3.5H20(III ) were prepared and analysed. Their hygr0sCopicity and Solubility was investigated. These compounds have high thermai Stability, as shown by their TG and DTA data. IR spectra show multi-dentate coordination of selenite to cations, due to considerable splitting of the asymmetric v3 and v4 bands of SeO32 -in the 780-730 cm ~ t and 420-325 cm-~ region.Tentative structures have been proposed involving bridging oxygen atoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2002
2002
2007
2007

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 10 publications
(7 reference statements)
0
2
0
Order By: Relevance
“…As result of the attempt, positional coordinates of six oxygen atoms were found (EXPO: R p = 6.48%). Additional oxygen atoms were not found despite the fact that Verma et al suggested a tentative structure of PbSeO 3 ·2H 2 O for a compound that was prepared at similar conditions . Finally, the anhydrous crystal structure was confirmed by the thermal studies (see section 4.2).…”
Section: Structure Determinationmentioning
confidence: 83%
See 1 more Smart Citation
“…As result of the attempt, positional coordinates of six oxygen atoms were found (EXPO: R p = 6.48%). Additional oxygen atoms were not found despite the fact that Verma et al suggested a tentative structure of PbSeO 3 ·2H 2 O for a compound that was prepared at similar conditions . Finally, the anhydrous crystal structure was confirmed by the thermal studies (see section 4.2).…”
Section: Structure Determinationmentioning
confidence: 83%
“…Thermogravimetric studies were carried out to confirm that the compound did not contained water and to compare the thermal decomposition of the both structures. Decomposition paths being presented in the literature are partly contradictory, as various types of dissociation routes are suggested. , In Figure two similarly behaving TG curves are displayed. The light gray curve was recorded from the β -type under nitrogen and the darker one from the α -type recorded under air.…”
Section: Resultsmentioning
confidence: 99%